Robots and women in manufacturing employment - Izaskun Zuazu-Bermejo (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2022)
Automation transforms the combination of tasks performed by machines and humans, and reshapes existing labour markets by replacing jobs and creating new ones. The implications of these transformations are likely to differ by gender as women and men concentrate in different tasks and jobs. This article argues that a gender-biased technological change framework will advance our understanding of the differentiated role of robots in labour market outcomes of women and men. The article empirically analyses the impact of industrial robots in gender segregation and employment levels of women and men using an industry-level disaggregated panel dataset of 11 industries in 14 developed and developing countries during 1993-2015. Within fixed-effects and instrumental variables estimates suggest that robotization increases the share of women in manufacturing employment. However, this impact hinges upon female labour force participation. As female labour participation rate increases, robots are associated with a negative effect of robotization in the female share of manufacturing employment. Results also show that the impact of robotization varies at different levels of economic development. The estimates point to a reducing employment effects of robotization, although the effect for women is larger. The results are robust to a variety of various sensitivity checks.
Keywords: C23; F16; J16; F14; 330; gender-biased technological change; robotization; manufacturing employment; gender industrial segregation